3(2.5y+8)*2y=31

Simple and best practice solution for 3(2.5y+8)*2y=31 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2.5y+8)*2y=31 equation:


Simplifying
3(2.5y + 8) * 2y = 31

Reorder the terms:
3(8 + 2.5y) * 2y = 31

Reorder the terms for easier multiplication:
3 * 2y(8 + 2.5y) = 31

Multiply 3 * 2
6y(8 + 2.5y) = 31
(8 * 6y + 2.5y * 6y) = 31
(48y + 15y2) = 31

Solving
48y + 15y2 = 31

Solving for variable 'y'.

Reorder the terms:
-31 + 48y + 15y2 = 31 + -31

Combine like terms: 31 + -31 = 0
-31 + 48y + 15y2 = 0

Begin completing the square.  Divide all terms by
15 the coefficient of the squared term: 

Divide each side by '15'.
-2.066666667 + 3.2y + y2 = 0

Move the constant term to the right:

Add '2.066666667' to each side of the equation.
-2.066666667 + 3.2y + 2.066666667 + y2 = 0 + 2.066666667

Reorder the terms:
-2.066666667 + 2.066666667 + 3.2y + y2 = 0 + 2.066666667

Combine like terms: -2.066666667 + 2.066666667 = 0.000000000
0.000000000 + 3.2y + y2 = 0 + 2.066666667
3.2y + y2 = 0 + 2.066666667

Combine like terms: 0 + 2.066666667 = 2.066666667
3.2y + y2 = 2.066666667

The y term is 3.2y.  Take half its coefficient (1.6).
Square it (2.56) and add it to both sides.

Add '2.56' to each side of the equation.
3.2y + 2.56 + y2 = 2.066666667 + 2.56

Reorder the terms:
2.56 + 3.2y + y2 = 2.066666667 + 2.56

Combine like terms: 2.066666667 + 2.56 = 4.626666667
2.56 + 3.2y + y2 = 4.626666667

Factor a perfect square on the left side:
(y + 1.6)(y + 1.6) = 4.626666667

Calculate the square root of the right side: 2.150968774

Break this problem into two subproblems by setting 
(y + 1.6) equal to 2.150968774 and -2.150968774.

Subproblem 1

y + 1.6 = 2.150968774 Simplifying y + 1.6 = 2.150968774 Reorder the terms: 1.6 + y = 2.150968774 Solving 1.6 + y = 2.150968774 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1.6' to each side of the equation. 1.6 + -1.6 + y = 2.150968774 + -1.6 Combine like terms: 1.6 + -1.6 = 0.0 0.0 + y = 2.150968774 + -1.6 y = 2.150968774 + -1.6 Combine like terms: 2.150968774 + -1.6 = 0.550968774 y = 0.550968774 Simplifying y = 0.550968774

Subproblem 2

y + 1.6 = -2.150968774 Simplifying y + 1.6 = -2.150968774 Reorder the terms: 1.6 + y = -2.150968774 Solving 1.6 + y = -2.150968774 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1.6' to each side of the equation. 1.6 + -1.6 + y = -2.150968774 + -1.6 Combine like terms: 1.6 + -1.6 = 0.0 0.0 + y = -2.150968774 + -1.6 y = -2.150968774 + -1.6 Combine like terms: -2.150968774 + -1.6 = -3.750968774 y = -3.750968774 Simplifying y = -3.750968774

Solution

The solution to the problem is based on the solutions from the subproblems. y = {0.550968774, -3.750968774}

See similar equations:

| 4c^2+-9=0 | | 6(a+2)=4[a-(10-a)] | | 2x^2(x-3y)-x(4-8x^2)= | | 4-3n= | | 2x=5y+8 | | 5x+10x=12 | | 10=2b+4 | | 35p+5d=25d+24m+10m | | 2m-8m/5=3m/45+14/3 | | 9x^2+-24x+16=0 | | 3.2x+2.6= | | 35p+10m=25d+24m+5d | | -2x-5y=-2 | | 5(5x-x)=-30x+25 | | 6+2x=2x+3 | | -2=7+a | | 23+-3= | | 3t+6/7t-7*14t-14/5t-10 | | 9x+8y=10.75 | | x/3=4x/21+2 | | 3/5k+7/10=11/15k-2/5 | | 9=2m | | 18x^2+-31xy+6y^2=0 | | 5x(5-x)=-30x+25 | | 9x-(2x+7)=35 | | -9x-7y=-1 | | 11x^2+-78x+7=0 | | 6a^2+-50ab+16b^2=0 | | 3x-y=19.6 | | -(4x+2)+4x+2=4 | | 8+c=3 | | 4x+8/3=-12 |

Equations solver categories